Synthesis and photophysical characteristics of polyfluorene polyrotaxanes - Farcas, Aurica; Tregnago, Giulia; Resmerita, Ana-Maria; Aubert, Pierre-Henri; Cacialli, Franco (Beilstein Journal of Organic Chemistry, 2015)
Two alternating polyfluorene polyrotaxanes (3·TM-βCD and 3·TM-γCD) have been synthesized by the coupling of 2,7-dibromofluorene encapsulated into 2,3,6-tri-O-methyl-β- or γ-cyclodextrin (TM-βCD, TM-γCD) cavities with 9,9-dioctylfluorene-2,7-diboronic acid bis(1,3-propanediol) ester. Their optical, electrochemical and morphological properties have been evaluated and compared to those of the non-rotaxane counterpart 3. The influence of TM-βCD or TM-γCD encapsulation on the thermal stability, solubility in common organic solvents, film forming ability was also investigated. Polyrotaxane 3·TM-βCD exhibits a hypsochromic shift, while 3·TM-γCD displays a bathochromic with respect to the non-rotaxane 3 counterpart. For the diluted CHCl3 solutions the fluorescence lifetimes of all compounds follow a mono-exponential decay with a time constant of ≈0.6 ns. At higher concentration the fluorescence decay remains mono-exponential for 3·TM-βCD and polymers 3, with a lifetime τ = 0.7 ns and 0.8 ns, whereas the 3·TM-γCD polyrotaxane shows a bi-exponential decay consisting of a main component (with a weight of 98% of the total luminescence) with a relatively short decay constant of τ1 = 0.7 ns and a minor component with a longer lifetime of τ2 = 5.4 ns (2%). The electrochemical band gap (ΔEg) of 3·TM-βCD polyrotaxane is smaller than that of 3·TM-γCD and 3, respectively. The lower ΔEg value for 3·TM-βCD suggests that the encapsulation has a greater effect on the reduction process, which affects the LUMO energy level value. Based on AFM analysis, 3·TM-βCD and 3·TM-γCD polyrotaxane compounds exhibit a granular morphology with lower dispersity and smaller roughness exponent of the film surfaces in comparison with those of the neat copolymer 3.
Keywords: energy band gaps; fluorescence lifetimes; permethylated cyclodextrins; polyfluorene; polyrotaxanes